2014
DOI: 10.1007/s00784-014-1339-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated insulin resistance in patients with recurrent aphthous stomatitis

Abstract: Patients who admitted the hospital with RAS might be screened for prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
2
4
0
6
Order By: Relevance
“…Further in this context, the recently reported observation by Takci et al of insulin resistance among patients with aphthous ulcers, especially when in the active stage, adds to the safety margin of our treatment. 19 Lastly, our methodology and results in this regard agree with other studies that utilized topical insulin twice daily for treatment of large area skin wounds for extended periods of time and did not report any side-effects during the study period. 7,10 To our knowledge, this work is the first controlled study using insulin topically on human oral mucosa for management of RAU.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Further in this context, the recently reported observation by Takci et al of insulin resistance among patients with aphthous ulcers, especially when in the active stage, adds to the safety margin of our treatment. 19 Lastly, our methodology and results in this regard agree with other studies that utilized topical insulin twice daily for treatment of large area skin wounds for extended periods of time and did not report any side-effects during the study period. 7,10 To our knowledge, this work is the first controlled study using insulin topically on human oral mucosa for management of RAU.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the small surface area of RAU (<10 mm in diameter), its limited duration, the once daily application and the small quantities of the medications used, we think that topical insulin is a safe agent for treatment of RAU in systemically healthy patients. Further in this context, the recently reported observation by Takci et al of insulin resistance among patients with aphthous ulcers, especially when in the active stage, adds to the safety margin of our treatment . Lastly, our methodology and results in this regard agree with other studies that utilized topical insulin twice daily for treatment of large area skin wounds for extended periods of time and did not report any side‐effects during the study period …”
Section: Discussionsupporting
confidence: 88%
“…A, E and C in serum and saliva of patients with RAS were signi cantly decreased, and the level of malondialdehyde (MDA) was signi cantly increased, which indicated that the non-enzymatic antioxidant capacity of patients with RAS was impaired [30]. Z. Takci et al showed that insulin resistance (IR) increased in patients with RAS, and IR was more prominent when the patients were in active stage [31]. Extracellular miR-20b-5p derived from exosome is a circulating biomarker associated with type 2 diabetes mellitus, which regulates insulin-stimulated glucose metabolism through AKT signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the role of oxidative stress in the etiopathogenesis of RAS, and despite some conflicting data, it seems that oxidative stress is significantly increased in patients with RAS (Tugrul et al, 2015). In a study by Takci et al (Takci et al, 2015) insulin resistance, the major characteristic of metabolic syndrome was found to be significantly higher in patients with RAS than in healthy controls. This is an interesting result because peripheral insulin resistance was explained as an outcome of endothelial dysfunction in Behc ßet's disease (Erdem et al, 2006).…”
Section: Oral Diseasesmentioning
confidence: 99%